CXCL9 as a Prognostic Inflammatory Marker in Early-Stage Lung Adenocarcinoma Patients - Zhang, Yanwei; Sun, Beibei; Hu, Minjuan; Lou, Yuqing; Lu, Jun; Zhang, Xueyan; Wang, Huimin; Qian, Jialin; Chu, Tianqing; Han, Baohui (Frontiers in Oncology, 2020)
Background: This study was performed to evaluate the value of inflammatory biomarkers in predicting the prognosis of early-stage (stage IA-IIB) lung adenocarcinoma. Methods: Ten inflammatory biomarkers were tested with a Luminex bead-based assay in early-stage lung adenocarcinoma patients who underwent resection. Results: A total of 152 early-stage lung adenocarcinoma patients were analyzed in this study. The mean patient age (SD) was 59.9 (9.4) years. In total, 58.6% of patients were females, and never smokers accounted for 84.0%. Lung adenocarcinoma patients with high CXCL9 levels had a 71% reduced risk of recurrence relative to patients with low CXCL9 levels (HR=0.29, 95% CI: 0.13–0.64, p=0.0021). After Bonferroni correction, CXCL9 remained significantly related to the risk of early-stage lung adenocarcinoma recurrence. Lung adenocarcinoma patients with high CXCL9 levels had an 80% reduced risk of death relative to patients with low CXCL9 levels (HR=0.20, 95% CI: 0.05–0.78, p=0.021), and those in the TCGA validation cohort were at a 29% reduced risk of death (HR=0.71, 95% CI: 0.45–0.99, p=0.044). Conclusion: Our results demonstrate for the first time that the CXCL9 level is a protective factor for both disease-free survival (DFS) and overall survival (OS) in early-stage lung adenocarcinoma patients.